African economic integration, potential and constraints for Algerian exports: Is Actfa a real opportunity for companies? - (:unkn) unknown (My University, 2021)
Trade integration in Africa becomes effective in 2021 with the launch of the African Commercial Free Trade Area (Acfta, and Zleca in french). This is reflected in the rapprochement between the existing economic communities and a gradual dismantling of tariffs in order to encourage trade and increase the share of intra-african trade. It also offers opportunities for business development in African markets. Through a qualitative exploratory study, this work aims to analyze the potential of the Actfa for Algerian exporting companies. The results show that significant resources have been put in place by the algerian authorities through numerous structuring projects in order to prepare the country for this membership. Nevertheless, many constraints remain in terms of institutional support, adaptation of fiscal and financial regulations and economic diplomacy.
Keywords: African Research